Novel predictor of pulmonary arterial hypertension: Monocyte to HDL cholesterol ratio. Issue 34 (26th August 2022) - Bilik, Mehmet Zihni; Oylumlu, Muhammed; Oylumlu, Mustafa; Acun, Baris; Arik, Baran; Arslan, Bayram; Acet, Halit; Polat, Nihat; Akil, Mehmet Ata
Abstract : Monocyte to HDL cholesterol ratio (MHR), lymphocyte to monocyte ratio (LMR), and neutrophil to lymphocyte ratio (NLR) have been proposed as novel systemic inflammatory markers. The aim of this study was to explore the association between MHR, LMR and NLR with pulmonary arterial hypertension (PAH). The study is a single-center, retrospective Cross-sectional study. The study group consisted of 73 patients with PAH and the control group 77 participants without cardiac pathology as determined by echocardiography. On admission, blood sampling to calculate MHR, LMR, NLR, and detailed clinical data were obtained. According to the Pearson test, systolic pulmonary artery pressure (PAP) value Higher MHR, NLR and lower LMR that indicates an enhanced inflammation were significantly increased in patients with PAH when compared with controls. Compared to many other inflammatory markers, these markers are widely available. positively correlated with the MHR and NLR (r:.35, P < .001 and r:.33, P < .001, respectively), but negatively correlated with LMR (r: −.26, P = .001). After multivariate logistic regression analysis, MHR, LMR, and NLR remained as significant predictors of PAH (OR: 2.651, 95% CI: 1.227–5.755, P = .007; OR: 0.647, 95% CI:0.450–0.931, P = .005; OR: 1.350, 95% CI: 1.054–1.650 P = .030, respectively).